Analysis on savings and credit cooperatives efficiency in Thailand: A data envelopment analysis (DEA) approach - Asawaruangpipop, Poramate; Suwunnamek, Opal (My University, 2014)
The microfinance institutions in Thailand were considered to be significant as the alternative financing source such as Savings and Credit Cooperatives (SCCs). While these institutions have been intensified in term of cooperative quantity and impact on entire economy, many SCCs' operations have still now been suffered from losses with negative returns and liquidity problems. This research therefore aims to investigate the efficiency of 732 SCCs in Thailand by using the databases of Cooperative Auditing Department, Ministry of Agriculture and Cooperatives of Thailand and evaluate SCCs' technical efficiencies on production and intermediation model by Data Envelopment Analysis (DEA) method. The efficiency evaluation results classified according to the types of cooperatives indicated that state enterprise cooperative had maximum quantity of efficient cooperatives and average efficiency score. When conducting the co-analysis on efficient cooperatives or best practiced cooperatives of each type of cooperative, it was found that private cooperatives had maximum efficiency in term of cooperative quantity and efficiency score. © 2014 Academic Journals Inc.
Keywords: Data envelopment analysis; Efficiency; Microfinance; Savings and credit cooperatives